Transmission Properties of Fabry–Pérot Filter Consisting of Silicon-Based High-Contrast Gratings - Wei Wang; Xumin Gao; Xiaojing Fang; Xin Li; Hongbo Zhu; Yongjin Wang (IEEE Photonics Journal, 2016)
In this paper, we design and theoretically investigate an ultracompact Fabry–Pérot filter (FPF) consisting of two silicon-based high-contrast gratings (HCGs). The filter is proposed for implemention on a double silicon-on-insulator (double-SOI) platform. By using the rigorous coupled wave analysis method, we examine and discuss the influences of various factors on the transmission properties of the filter. The location of the transmission peak is capable of being tuned efficiently by changing the grating period, thickness, duty cycle, or filter cavity length. An ultrahigh quality factor (e.g., as high as 625960) can be readily achieved by merely choosing the appropriate grating period or thickness. Moreover, with increasing silicon substrate thickness, the modulation effect of the substrate is capable of decomposing the transmission peak into a bundle of subpeaks. In addition, structural differences between the two HCGs may degrade the peak transmittivity severely. In a word, this paper is devoted to a systematic report on the particular transmission properties of the filter and, thus, provides a clear picture of its overall performance, which is highly important for its practical design and applications.